2018
DOI: 10.1186/s41021-018-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of yeast glutaredoxin Grx6 protein produced in Escherichia coli

Abstract: BackgroundGrx6 is a yeast Golgi/endoplasmic reticulum protein involved in iron-sulfur binding that belongs to monothiol glutaredoxin-protein family. Grx6 has been biochemically characterized previously. Grx6 contains a conserved cysteine residue (Cys-136). Depending on the active-site sequences, Grxs can be classified to classic dithiol Grxs with a CXXC motif known as classes II and monothiol Grxs with a CXXS motif known as classes I, and Grx6 belongs to the class I with a CSYS motif.ResultsOur results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies showed that some GRX proteins, such as Arabidopsis GRXC1, could form homodimers by ligating iron–sulfur clusters, leading to GRX inactivation (Riondet et al., 2012). When this kind of GRXs was expressed in E. coli , part of the recombinant GRXs existed as active monomeric proteins, and the other part as inactive iron–sulfur homodimers or/and tetramers (Abdalla et al., 2018; Lillig et al., 2005; Riondet et al., 2012). In this study, to obtain monomeric GRXs, all GRX proteins purified by an affinity chromatography column (Amylose Resin column or Nickel–Sepharose High Performance column) were further separated by size‐exclusion chromatography (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that some GRX proteins, such as Arabidopsis GRXC1, could form homodimers by ligating iron–sulfur clusters, leading to GRX inactivation (Riondet et al., 2012). When this kind of GRXs was expressed in E. coli , part of the recombinant GRXs existed as active monomeric proteins, and the other part as inactive iron–sulfur homodimers or/and tetramers (Abdalla et al., 2018; Lillig et al., 2005; Riondet et al., 2012). In this study, to obtain monomeric GRXs, all GRX proteins purified by an affinity chromatography column (Amylose Resin column or Nickel–Sepharose High Performance column) were further separated by size‐exclusion chromatography (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…It found that the definition of RBV is more extensive, and the study found that the estimator is more robust and more effective than the RV. Through empirical research on the data of the Shenzhen Stock Exchange and the Shanghai Composite Index, they confirmed that RBV has indeed achieved a more accurate estimation of stock market yield fluctuations 8 . By calculating the extremely poor price of high-frequency data, Christensen and Podolskij proposed another volatility estimator, the RRV estimator.…”
Section: Introductionmentioning
confidence: 93%
“…Through empirical research on the data of the Shenzhen Stock Exchange and the Shanghai Composite Index, they confirmed that RBV has indeed achieved a more accurate estimation of stock market yield fluctuations. 8 By calculating the extremely poor price of high-frequency data, Christensen and Podolskij proposed another volatility estimator, the RRV estimator. RRV has been used to reveal more useful information by exploiting the extremes of the entire price process.…”
Section: Introductionmentioning
confidence: 99%
“…193 It has glutathione-S-transferase and glutathione-dependent oxidoreductase activities. [215][216][217][218][219] Grx6 regulates the glutathionylation of proteins in the ER and Golgi, and controls the ratio of oxidized and reduced glutathione to protect the cell against oxidative stress.…”
Section: Endoplasmic Reticulum (Er)mentioning
confidence: 99%